CHEMICAL EVOLUTION OF SEAWATER DURING THE PHANEROZOIC: IMPLICATIONS FROM THE RECORD OF MARINE EVAPORITES - Horita J.; Zimmermann H.; Holland H.D. (My University, 2002)
The chemical evolution of seawater during the Phanerozoic is still a matter of debate. We have assembled and critically analyzed the available data for the composition of fluid inclusions in marine halite and for the mineralogy of marine evaporites. The composition of fluid inclusions in primary marine halite reveals two major long-term cycles in the chemistry of seawater during the past 600 myr. The concentration of Mg2+, Ca2+, and SO42− has varied quite dramatically. The Mg2+ concentration in seawater during most of the early Paleozoic and Jurassic to Cretaceous was as low as 30 to 40 mmol/kg H2O; it reached maximum values ≥50 mmol/kg H2O during the Late Neoproterozoic and Permian. The Ca2+ concentration in seawater during the Phanerozoic has reached maximum values two to three times greater than the concentration in seawater today (10.6 mmol/kg H2O), whereas SO42− concentrations may have been as low as 5 to 10 mmol/kg H2O (a third to a fifth of the modern value) during the Jurassic and Early Paleozoic. The Mg2+/Ca2+ ratio in seawater ranged from 1 to 1.5 during the early to middle Paleozoic and Jurassic-Cretaceous to a near-modern value of 5.2 during the Late Neoproterozoic and Permian. This change in seawater Mg2+/Ca2+ ratio is consistent with the notion of alternating “calcite-aragonite seas” recorded in oölites and marine carbonate cements.Several models have been proposed to explain the chemical evolution of seawater. These have invoked significant changes in one or more of the major geochemical processes that control the composition of seawater. The pattern and magnitude of the variations in the composition of seawater proposed in this study are similar to those proposed elsewhere that suggest that seawater fluxes through midocean ridges have played a major role in the evolution of seawater during the past 600 myr. Two Phanerozoic supercycles of the Earth’s exogenic processes were recognized in the literature that are caused by mantle convection and plate activity. The composition of seawater has apparently undergone dramatic secular changes in phase with these supercycles and as a consequence of biological evolution. Analyses of fluid inclusions containing unevaporated seawater and a better understanding of the processes that affect the composition of seawater are needed to refine our understanding of the history of Phanerozoic seawater.